Linear Psoriasis - A Case Report - Ana Brinca; F. Santiago; D. Serra; P. Andrade; R. Vieira; A. Figueiredo (Karger Publishers, 2011)
A 56-year-old woman presented with a 3-month history of erythematous plaques covered by scales and limited to the right side of her body. The plaques were arranged along Blaschko's lines with a marked mid-line cutoff. The histopathologic analysis of a skin biopsy in conjunction with the anamnesis allowed the diagnosis of linear psoriasis. Our patient showed a good clinical response to antipsoriatic treatment.